Dynamic Sea Level Variation From GNSS: 2020 Shumagin Earthquake Tsunami Resonance and Hurricane Laura. Issue 4 (16th February 2021) - Larson, Kristine M.; Lay, Thorne; Yamazaki, Yoshiki; Cheung, Kwok Fai; Ye, Lingling; Williams, Simon D.P.; Davis, James L.
Abstract: Rapid determination of sea level variations caused by tsunamis or major storm surges is important for coastal hazard mitigation. Coastal Global Navigation Satellite Systems (GNSS) stations at elevations less than ∼300 m can record time‐varying sea level changes by tracking signals that reflect from the sea surface, relative to direct signals from the satellites. We demonstrate that such GNSS stations can rapidly provide local sea level measurements for a near‐field tsunami, involving many hours of shelf resonance generated by the 2020 Shumagin earthquake as well as for the storm surge accompanying passage of the eye of Hurricane Laura over the Louisiana Coast. Coastal GNSS stations deployed to measure tectonic deformation and co‐seismic displacements can inexpensively augment the spatial sampling provided by tide gauges for measuring tsunami‐induced coastal resonance and storm surges. This information can guide response activities during the crucial initial hours of an event. Plain Language Summary: Sea level variations caused by tsunamis and storm surges must be measured as quickly as possible for public safety warnings. This work uses examples from the 2020 Shumagin Island tsunami and the Hurricane Laura storm surge to demonstrate that Global Navigation Satellite System instruments installed along coastal regions to measure plate tectonic motions are also capable of providing sea level information in near real‐time. Key Points: Coastal Global Navigation Satellite Systems (GNSS) stations detect sea surface reflections that capture real‐time sea level variations due to tides, tsunami waves, and storm surges Repeated tsunami surges of ∼30 cm are observed around the Shumagin Islands for more than 10 h after the 2020 Shumagin earthquake A peak storm surge of ∼2.5 m was observed as the eye of Hurricane Laura passed over a GNSS station on the Louisiana Coast